Expressionistic Eidology: Paradigm of the Archetype - Яструбецька, Галина Іванівна; Yastrubetska, Halyna I. (Polskie Towarzystwo Teologiczne w Krakowie, 2013)
The article “Expressionistic Eidology: Paradigm of the Archetype” is part of the research project - “Expressionism in Ukrainian Literature”. The aim of the study is to highlight the archetype as an expressionistic and stylistic universal. Expressionism has been treated here primarily as poetics, with the focus on the aesthetic nature of the word and on the author’s spiritual intentions. The objective of the article has been to broaden and complement the scope of representations about theoretical fundamentals of expressionism in literature. It enhances the chance of a deeper understanding of the nature and character of this artistic phenomenon. First of all, it has been brought about by the shift of literary vectors in the axiological expressionistic paradigm from the universal, ontological basis and of the role of the phenomenon to social and historical grounds; consequently, it results in the of narrowing the semantic and chronological scope of expressionism. The methodological background of the research draws upon the studies by Ukrainian and European scholars such as V.Budny, O.Valtsel, H.G.Gadamer, C.P.Estes, M.Ilnytsky, U.Kovaliv, M.Moklytsia, R.Pihmanets, L.Ushkalov, I.Franko. The structural-typological method is used for writing this article. The key findings of the research comprise emphasis on expressionism as poetics with focus on the aesthetic nature of the word and the author’s spiritual intensions. The article highlights the idea of literary expressionism as a certain primal essence established in the profundity of human spirit, independent of conscious activity, and of social and historical conditions, but it is objectified via a human being (an artist) due to intensive inner work that is reflected in the fundamental changes of the structure of consciousness. The article underlines the paramount importance of the archetype for expressionism as a unique opportunity to reach the ultimate expression of feelings, emotions and experience concentrated in one entity as evidence that a person is receptive to mystical powers which create the universe and it proves that the celestial idea as a regulatory standard is hidden in expressionism. The Life-Death antinomy is represented as one of the dominant units in the archetypal system of expressionism; since it creates the most emotional intensity and increases the dynamics of the text. To support these ideas the phenomenological data from the works of Ukrainian prose writers such as Vasyl Stefanyk (1871-1936) and Valerian Pidmohylny (1901-1937) have been used. The results of the research focus on emphasizing one of the expressionistic universals such as the archetype, and on finding the motivational statement of this idea through analysis of V.Stefanyk and V. Pidmohylny’s conceptual foundations. The results of the research may be employed in the study of literary theory and history of literature as well as might be of use for further development of literary studies (for scholars and students). The novelty of the article includes recognition and evaluation of the archetype as one of the fundamental categories in literary expressionism.
Яструбецька Галина Іванівна - кандидат філологічних наук, доцент кафедри української літератури Східноєвропейського національного університету ім. Лесі Українки
Keywords: Expressionism; stylistic universal; eidology; archetype; tanatography; V.Stefanyk; V.Pidmohylny